Characterization of genome methylation patterns in the desert locust Schistocerca gregaria - Falckenhayn, Cassandra; Boerjan, Bart; Raddatz, Günter; Frohme, Marcus; Schoofs, Liliane; Lyko, Frank (The journal of experimental biology, 2013)
Skip to Next Section - DNA methylation is a widely conserved epigenetic modification. The analysis of genome-scale DNA methylation patterns in various organisms suggests that major features of animal methylomes are widely conserved. However, based on the variation of DNA methyltransferase genes in invertebrates, it has also been proposed that DNA methylation could provide a molecular mechanism for ecological adaptation. We have now analyzed the methylome of the desert locust, Schistocerca gregaria, which represents an organism with a high degree of phenotypic plasticity. Using genome-scale bisulfite sequencing, we show here that the S. gregaria methylome is characterized by CpG- and exon-specific methylation and thus shares two major features with other animal methylomes. In contrast to other invertebrates, however, overall methylation levels were substantially higher and a significant fraction of transposons was methylated. Additionally, genic sequences were densely methylated in a pronounced bimodal pattern, suggesting a role for DNA methylation in the regulation of locust gene expression. Our results thus uncover a unique pattern of genome methylation in locusts and provide an important foundation for investigating the role of DNA methylation in locust phase polyphenism.
Gesehen am 25.02.2021